Nexus between Digital Competency Level and Performance Level of State Civil Apparatus - Setyawan, Yogi Febri; Gumilar, Annas; Apriliani, Ima; Bhaskoro, Ferdian (Journal La Sociale, 2025)
This study analyzes the relationship between digital competence and performance of the State Civil Apparatus (ASN) in supporting the Digital Transformation agenda in Indonesia. Digital competency is measured using five variables from the DigComp 2.2 framework: Information and Data Literacy, Communication and Collaboration, Digital Content Creation, Digital Security and Problem Solving. Meanwhile, ASN performance is assessed through three variables: Task Performance, Contextual, and Adaptive. Data was obtained from 206 ASN respondents through questionnaires and analyzed using Confirmatory Factor Analysis (CFA). The results showed a significant positive relationship between digital competence and ASN performance, with a correlation of 0.769. The Digital Content Creation and Problem-Solving variables had the lowest competency levels, while the 41-45, 36-40, 51-55, and 56-62 years age groups showed a significant percentage of low categories. This research confirms the need to increase digital competence in improving ASN performance to support the success of digital transformation in the public sector.